2006
DOI: 10.1159/000096276
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms in Machado-Joseph Disease (SCA3) Patients and Their Relatives

Abstract: Objectives: It was the aim of this study to determine the depression scores of Machado-Joseph disease (MJD) patients, their spouses, and individuals at 50% risk for MJD, and second, to verify the existence of a correlation between depressive symptoms and the degree of motor incapacitation. Subjects and Methods: Two hundred and forty-six individuals aged ≧18 years were studied: 79 MJD patients (group 1), 43 spouses of MJD patients (group 2), 80 individuals at risk for MJD (group 3), and a control group (group 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 50 publications
3
42
1
Order By: Relevance
“…OT improved the depressive symptoms of SCA3 patients, which are an important clinical problem already shown to be common among these patients (12 incapacitation levels observed in previous studies was not found in the present sample (12). We speculate that our lack of association was due to the recruitment of patients with relatively shorter disease duration and lower impact on their capabilities.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…OT improved the depressive symptoms of SCA3 patients, which are an important clinical problem already shown to be common among these patients (12 incapacitation levels observed in previous studies was not found in the present sample (12). We speculate that our lack of association was due to the recruitment of patients with relatively shorter disease duration and lower impact on their capabilities.…”
Section: Discussioncontrasting
confidence: 50%
“…All of these findings lead to a progressive burden and incapacitation. In addition, depressive symptoms are rather frequent and may be related to the inexistence of an effective treatment (12). In SCA3, depressive scores have been associated with the level of incapacitation, conditions that probably reinforce each other.…”
Section: Introductionmentioning
confidence: 99%
“…First, BDI was the only tool available for the evaluation of the subjects’ depression. The degree of depression would be accurate when assessed by a series of tools related to patients’ psychiatric symptoms, although BDI had also been used solely in several studies on the depression in SCA3 patients [15, 16, 18-21]. Second, although in our cohort, the frequency of depression was extremely high, we lacked an age- and sex-matched control group to compare between the 2 groups.…”
Section: Discussionmentioning
confidence: 97%
“…The severity of the subjects’ depression in SCA3 patients was evaluated by Beck depression inventory (BDI), which was solely and widely used for evaluating the depression of SCA3 patients [15, 16, 18-21]. Since the participating subjects were Chinese, the adopted BDI in Chinese version was found to exhibit optimal sensitivity and specificity in recognizing the depression among the ­Chinese-speaking population [22].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation